(untitled) (Proceeding of SINERGY, 2026)
In 2023, online shopping transaction value has reached IDR 1,100 trillion, in which 75,19% of those were done by Cash on Delivery (COD) transaction method. However, National financial literacy index in 2023 was 65.43%, which theoretically should encourage the use of digital payments. This research seeks to investigate the impact of Financial Literacy (FL) and Digital Payment Trust (DPT) on Cash on Delivery (COD) preference and its implication for perception of Last Mile Delivery (LMD) performance. Using an explanatory quantitative approach with PLS-SEM analysis on 60 respondents, the result shows that FL has positive and significant impact on LMD through COD preference (β=0,241; p=0,001). This supports the notion that financially literate consumers choose COD as a risk mitigation plan to gain full control over transaction. Conversely, DPT has negative and significant impact on LMD through COD preference (β=-0,376; p=0,001). This behavior appears due to COD as a considered adaptation strategy and substitute for trust when the reliability of digital payment systems in the online shopping ecosystem is questioned. Furthermore, COD preference has positive and significant impact on perception of LMD performance (β=0,613; p=0,001) because direct face-to-face interaction provide a more tangible sense of security for consumers. This research concludes that COD preference is an intervening variable that explains why high financial literacy does not necessarily encourage payment digitalization, but rather strengthens cash methods as measurable risk protection in the logistics ecosystem, particularly for online shopping.